Contribution to the phylogeny and a new species of Coccodiella (Phyllachorales) - Mardones Hidalgo, Melissa (2017)
Coccodiella is a genus of plant-parasitic species in the family Phyllachoraceae (Phyllachorales, Ascomycota), i.e., tropical tar spot fungi. Members of the genus Coccodiella are tropical in distribution and are host-specific, growing on plant species belonging to nine host plant families. Most of the known species occur on various genera and species of the Melastomataceae in tropical America. In this study, we describe the new species C. calatheae from Panama, growing on Calathea crotalifera (Marantaceae). We obtained ITS, nrLSU, and nrSSU sequence data from this new species and from other freshly collected specimens of five species of Coccodiella on members of Melastomataceae from Ecuador and Panama. Phylogenetic analyses allowed us to confirm the placement of Coccodiella within Phyllachoraceae, as well as the monophyly of the genus. The phylogeny of representative species within the family Phyllachoraceae, including Coccodiella spp., graminicolous species of Phyllachora and taxa with erumpent to superficial stroma from several host families, suggests that the genus Phyllachora might be polyphyletic. Furthermore, tar spot fungi with superficial or erumpent perithecia seem to be restricted to the family Phyllachoraceae, independently of the host plant. We also discuss the biodiversity and host-plant patterns of species of Coccodiella worldwide.